RADT-12. PRE- AND POST-OPERATIVE RADIATION TREATMENT PLANNING FOR PATIENTS RECEIVING STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASES: A VOLUMETRIC ANALYSIS. (14th November 2022) - Ho, Cindy; Perlow, Haley; Ritter, Alex; Gokun, Yevgeniya; Matsui, Jennifer; Wang, Joshua; Damante, Mark; Blakaj, Dukagjin; Beyer, Sasha; Thomas, Evan; Lonser, Russell; Hardesty, Douglas; et al.
Abstract: BACKGROUND: Pre-operative stereotactic radiosurgery (SRS) has emerged as a recent treatment option to treat large or symptomatic brain metastases. Compared to post-operative SRS, pre-operative treatment may reduce rates of radiation necrosis (RN) and meningeal disease through treating a smaller treatment volume and by preventing post-operative tumor seeding. We hypothesize that pre-operative radiation volumes will be smaller than post-operative volumes, which in turn may lead to a decreased treatment morbidity. METHODS: A retrospective analysis was conducted and patients who had surgical resection and post-operative SRS or fractionated stereotactic radiosurgery (FSRT) for a posterior fossa brain metastasis were eligible for inclusion. Both pre-operative and post-operative MRIs were required to allow for accurate radiation target delineation. A pre-operative tumor volume was added for each patient, and the post-operative clinical treatment volume (CTV) used for radiation treatment was included. Pre-operative tumor and post-operative cavity volumes were compared using Wilcoxon signed rank test. RESULTS: 28 patients who received post-operative SRS or FSRT from 1/1/2016-12/31/2020 were included in this analysis. The mean pre-operative tumor volume was 14.9 ccs, and the mean post-operative CTV was 21.0 ccs (p < 0.01). 75% of patients had a smaller initial tumor size compared to the post-operative CTV used for radiation treatment planning. For patients with at least 4 follow up MRIs (n = 8), the size of the post-operative cavity progressively decreased with a mean initial cavity volume of 18.9 ccs and mean follow up volumes of 8.1, 7.1, 6.9, and 6.2 ccs. CONCLUSIONS: In this study evaluating patients who received post-operative SRS, the pre-operative tumor volume was lower than the post-operative CTV for most patients. Previous studies including PROPS-BM have shown how pre-operative treatment may reduce the risk of RN because smaller radiation volumes are used. Pre-operative radiosurgery for patients with brain metastases requires prospective validation.